Endurance and gait speed relationships with mild cognitive impairment and dementia. Issue 1 (9th February 2022) - Windham, Beverly Gwen; Parker, Sara B.; Zhu, Xiaoqian; Gabriel, Kelley Pettee; Palta, Priya; Sullivan, Kevin J.; Parker, Kirby G.; Knopman, David S.; Gottesman, Rebecca F.; Griswold, Michael E.; Mosley, Thomas H.
Abstract: Introduction: Slower mobility is associated with mild cognitive impairment (MCI) and dementia. We examined the interaction of endurance with gait speed on prevalent MCI and dementia. Methods: Cross‐sectional multinomial regression in the ARIC cohort (n = 2844 participants; 71 to 94 years; 44% men; 18% Black persons) with cognitive status (normal/MCI/dementia), 4 m gait speed, and endurance (2 minute walk [2MW]). Results: Faster gait speed (up to but not above 1 m/s) and better 2MW were separately associated with lower dementia risk. Good performance in both (2MW = 200 m, gait speed = 1.2 m/s) was associated with 99% lower dementia (Relative Prevalence Ratio [RPR] = 0.01 [95% CI: 0.0 to 0.06]) and 73% lower MCI, RPR = 0.27 (0.15 to 0.48) compared to poor performance in both (2MW = 100 m, gait speed = 0.8 m/s). Models incorporating a gait speed‐by‐2MW interaction term outperformed gait speed‐only models ( P  < .001). Discussion: Gait speed relationships with dementia diminish at faster gait speeds. Combining endurance with gait speed may yield more sensitive markers of MCI and dementia than gait speed alone.